Pengaruh Pembelajaran Berbasis Masalah Terhadap Pemahaman Siswa tentang Nasionalisme dan Patriotisme - Hendra Prasetia (DIDAKTIKA: Jurnal Pendidikan Sekolah Dasar, 2019)
In this study aims to determine the effect of problem-based learning models on students' understanding of nationalism and patriotism of elementary school students as citizens. This type of research is an experimental study in the form of a pretest-posttest control group design research design. Hypothesis testing results explain the calculated t value obtained is equal to 5,216 and a significance value of 0,000, the hypothesis testing results indicate that the calculated t value obtained is greater than the t value in the table (5.216 2.408) while the significance value is smaller than the α value (0,000 0.05). Based on these results, the hypothesis is accepted, meaning that there is a significant influence between problem-based learning, on students' understanding of nationalism and patriotism of elementary school students as citizens.